YOUTHS’ UNEMPLOYMENT AND CRIME CONTROL: AN ANALYSIS OF NIGERIAN EXPERIENCE - Alabi, T. (European Scientific Journal, ESJ, 2014)
Sub-Saharan Africa population is characterized with young people. Economic active population group constitutes an average of 53% of the total population of the region for the past two decades as reported by the World Bank (2011). Over 40 % of these youths are without jobs or stable economic income. Also, 64.1% and 50.7% of the region’s total youth population live below U.S1.2 per day. The implications of characteristics of the population are very important. Youth unemployment is a global problem affecting both developed and developing countries alike. But while the developed countries are taking the threat seriously and restructuring their education and social security systems to abate its growth and escape the eminent catastrophic retrenchments, Nigeria seem not to be doing enough. This paper therefore examines the youths’ unemployment situation and its connection to growing crime wave in Nigeria. Literature is extensively reviewed; methodology is based on the exhaustive consultation of journals and records.